2021
DOI: 10.1186/s12936-021-03748-5
|View full text |Cite
|
Sign up to set email alerts
|

Setting-up a cross-border action-research project to control malaria in remote areas of the Amazon: describing the birth and milestones of a complex international project (Malakit)

Abstract: Background In French Guiana, gold miners working illegally represents a major reservoir of malaria. This mobile population, mainly of Brazilian descent, enters the French Guianese forest from neighbouring countries, Suriname and Brazil. A complex and innovative intervention was piloted as a cooperation with the three involved countries involved to control malaria in this specific population. The principle was that health workers called “facilitators” provide the participants with a self-diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…An innovative research project called Malakit focused on this neglected population which has been identified as a key host and a barrier to the elimination of the disease [ 25 27 ]. This international collaborative project aimed at evaluating the effectiveness of the preventive distribution of self-diagnosis and self-treatment kits, combined with information and training by facilitators, to gold miners , at resting sites on the borders, to be used when they were unable to rapidly consult a health care provider [ 26 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…An innovative research project called Malakit focused on this neglected population which has been identified as a key host and a barrier to the elimination of the disease [ 25 27 ]. This international collaborative project aimed at evaluating the effectiveness of the preventive distribution of self-diagnosis and self-treatment kits, combined with information and training by facilitators, to gold miners , at resting sites on the borders, to be used when they were unable to rapidly consult a health care provider [ 26 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…An innovative case management approach, called Malakit, was developed and implemented between 2018 and 2020 resulting from collaboration between Cayenne Hospital (FG), Suriname, and Brazil, to address malaria diagnosis and effective treatment of clandestine gold miners in FG. Ultimately, these efforts aimed to reduce the risk of emergence of resistant Plasmodium falciparum posed by the use of inappropriate treatment by the target population [13][14][15][16][17] . This project consisted in distributing kits containing malaria self-tests and Artemisinin-based combination therapy (ACT) to be used in the gold mining areas in FG, as well as training on malaria and how to correctly self-diagnose and self-treat.…”
Section: Discussionmentioning
confidence: 99%
“…Malakit is an international and multicentric interventional study with a quasi-experimental design, based on a single group intervention and an independent pre-and post-intervention evaluation survey including participants regardless of their participation or non-participation in the Malakit intervention. The methodology has been previously published 14,17 , and further details are available at www.malakitproject.org.…”
Section: Malakit Projectmentioning
confidence: 99%
See 2 more Smart Citations